Reduction of cardiac adipose tissue volume with short‐term empagliflozin treatment in patients with type 2 diabetes: A substudy from the SIMPLE randomized clinical trial. Issue 3 (3rd January 2023) - Brandt‐Jacobsen, Niels H.; Jürgens, Mikkel; Hasbak, Philip; Gæde, Peter; Rossing, Peter; Rasmussen, Jon J.; Andersen, Camillla Fuchs; Forman, Julie L.; Faber, Jens; Inzucchi, Silvio E.; Gustafsson, Finn; Schou, Morten; et al.
Abstract: Objective: Ectopic accumulation of cardiac adipose tissue volume (CAT) has been associated with cardiac remodelling and cardiac dysfunction in type 2 diabetes and may be a future therapeutic target. In this substudy from the SIMPLE‐trial, we investigated short‐term empagliflozin therapy's effects on CAT in patients with type 2 diabetes. Research design and Methods: Between 4 April 2017 and 11 May 2020, we randomized 90 patients with type 2 diabetes and established or high risk of cardiovascular disease to 25 mg empagliflozin or placebo for 13 weeks. The substudy focused on change in CAT evaluated by images acquired during 82 Rubidium‐positron emissions tomography/computed tomography. The analysis included 78 patients who had at least one scan. Furthermore, we report on the relation to the concurrent effects on left ventricular mass, end‐diastolic volume and end‐systolic volume, body composition and glucometabolic status. Results: Mean ± SD baseline CAT was 258.5 ± 117.9 ml. Empagliflozin reduced CAT after 13 weeks by 12.41 ml [95% CI (−23.83 to −0.99), p = .034] as compared with placebo. Similarly, left ventricular mass [−5.16 g, 95% CI (−8.80 to −1.52), p = .006], end‐diastolic volume and end‐systolic volume decreased with empagliflozin. In addition, significant improvements were observed in body composition, with reduced total fat mass, and in measures of glucose and lipid metabolism. However, no correlation was observed between changes in CAT and changes in cardiac parameters and change in CAT appeared mediated primarily by concurrent change in weight. Conclusions: Empagliflozin provides an early reduction of CAT; however, no association was observed with concurrent changes in cardiac volumetrics.